Industry and innovation, a fintech bet on economic development in Venezuela Case: Clabe ganadera (Gestión y Gerencia, 2024)
Economic development is assumed today from the sustainable development approach, which is why it is strategically linked to the Sustainable Development Goals (SDG) 2030, specifically SDG 9 Industry, innovation and infrastructure that is committed to triple impact business models (economic, social and environmental). The livestock sector in Venezuela has the case of Clabe Ganadera, which is recognized as a crowdfarming fintech company, under the concept of triple impact. Studying its rarity is pertinent to the nature of the interpretive paradigm, qualitative approach, case study method, interview technique with key informants and treatment of qualitative data in coding procedures, with the support of the Atlas.Ti program. The findings show an example of a successful case of a Venezuelan company that disrupts traditional livestock farming, from the crowdfarming business model, combined with the modality of technological tools, collaborative and alternative economy, credibility and trust in the consolidation of the prior agriculture work, communication strategy, innovative monitoring and control management, learning from ranchers-collaborators, social contribution to nearby communities, positive environmental practices and moral commitment to betting on the countryside and on Venezuela as a country with potential where young people continue doing good things.
Keywords: Fintech; livestock industry; innovation; ODS